2020
DOI: 10.1039/c9ra09985a
|View full text |Cite
|
Sign up to set email alerts
|

Metal oxide QD based ultrasensitive microsphere fluorescent sensor for copper, chromium and iron ions in water

Abstract: Herein we developed a rapid, cheap, and water-soluble ultra-sensitive ZnO quantum dot (QD) based metal sensor for detecting different hazardous metal ions up to the picomolar range in water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…Zhao et al and others reported that ZnO QDs exhibit absorption peaks from 250 to 400 nm. 7,47,48 Therefore, the shoulder position can be taken as evidence that the ZnO QDs are formed and assigned to the intrinsic band-gap of Zn-O absorption. 47 The high-intensity shoulder of the APTES/ ZnO QDs can be referred to APTES coated surface of ZnO QDs from surface defects and is related to the particle size effect.…”
Section: Surface Charges and Optical Propertiesmentioning
confidence: 99%
“…Zhao et al and others reported that ZnO QDs exhibit absorption peaks from 250 to 400 nm. 7,47,48 Therefore, the shoulder position can be taken as evidence that the ZnO QDs are formed and assigned to the intrinsic band-gap of Zn-O absorption. 47 The high-intensity shoulder of the APTES/ ZnO QDs can be referred to APTES coated surface of ZnO QDs from surface defects and is related to the particle size effect.…”
Section: Surface Charges and Optical Propertiesmentioning
confidence: 99%
“…[166] Another device is commercialised by Hatch instruments under the name EZ Series Online Analyzer for the online monitoring of Aluminium, Arsenic, Boron, Chromium, Copper, Iron, Manganese and Zinc in water. Model EZ6000/6001/6100/6101 is used for the detection of Arsenic in ZnO quantum dot 0.0834 μg/L & 2.34 μg/L fluorescence Cr(VI), Fe(III), Cu(II) [154] hydrous ferric oxide 0.6 μg/L Plasmon resonance As(III) and As(V) [155] multi-responsive block polymer brush PMAzo-PDMAEMA-SBA-15 [159] Poly(Py-co-OT)/CoFe2O4/NF 0.0087 μg/L 0.02-2000μg/L Pb(II) [160] amino group on magnetic Nano-adsorbent 10 μg/L Paper-based lateral flow immunoassays Pb(II) [161] NHAP/ionophore/ Nafion-modified 0.2 μg/L 0.2 μg/L to 160 μg/L ASV Pb(II) [162] Macro-/mesoporous polymer carbon-based monolithic cage-like template 0.3 μg/L 0-500 μg/L fluorimetry Co(II) [163] Phytic acid doped polyaniline nanofibers 0.02 μg/L and 0.05 μg/L 0.05-60 μg/L and 0.1-60 μg/L DPASV Cd(II) and Pb(II) [164] black phosphorus (BP) integrated tilted fiber grating 0.25 μg/L 0.1 to 1.5 × 10 7 μg/L polarization Pb(II) [165] ChemistrySelect water on gold electrode using stripping voltammetry. The weight of the device is 25 kg and dimensions are approximately in the range of 50 cm × 50 cm.…”
Section: Commercial Sensor Devicesmentioning
confidence: 99%
“…Though the device is portable; the electrodes are not disposable. Therefore, recently the same device consisting of ZnO quantum dot 0.0834 μg/L & 2.34 μg/L fluorescence Cr(VI), Fe(III), Cu(II) [154] hydrous ferric oxide 0.6 μg/L Plasmon resonance As(III) and As(V) [155] multi-responsive block polymer brush PMAzo-PDMAEMA-SBA-15 [159] Poly(Py-co-OT)/CoFe2O4/NF 0.0087 μg/L 0.02-2000μg/L Pb(II) [160] amino group on magnetic Nano-adsorbent 10 μg/L Paper-based lateral flow immunoassays Pb(II) [161] NHAP/ionophore/ Nafion-modified 0.2 μg/L 0.2 μg/L to 160 μg/L ASV Pb(II) [162] Macro-/mesoporous polymer carbon-based monolithic cage-like template 0.3 μg/L 0-500 μg/L fluorimetry Co(II) [163] Phytic acid doped polyaniline nanofibers 0.02 μg/L and 0.05 μg/L 0.05-60 μg/L and 0.1-60 μg/L DPASV Cd(II) and Pb(II) [164] black phosphorus (BP) integrated tilted fiber grating 0.25 μg/L 0.1 to 1.5 × 10 7 μg/L polarization Pb(II) [165] ChemistrySelect SPE fabricated by DropSense are deployed which can be disposed off after use. [166] Another device is commercialised by Hatch instruments under the name EZ Series Online Analyzer for the online monitoring of Aluminium, Arsenic, Boron, Chromium, Copper, Iron, Manganese and Zinc in water.…”
Section: Commercial Sensor Devicesmentioning
confidence: 99%
“…Consequently, the presence of this species in drinking water is regulated through the total chromium, whose maximum contaminant Level is 50 μg/L. Cr(VI) recommended maximal permissible limit (MPL) in the surface water is regulated to 2 mg/L and to 0.1 mg/L in drinking water [9][10][11][12][13]. Naturally occurring Cr(VI) is found in ground and surface waters at values above 50 μg/L [6,14].…”
Section: ■ Introductionmentioning
confidence: 99%